Cenários de um paisagismo ecológico para o igarapé da fortaleza – parque do igarapé - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2014)
This paper examines the area Igarapé da Fortaleza on the border of the municipalities of Santana and Macapá on the AP 010 highway, seeking for a project solution that harmonizes the economic activity related to the sale of fish and açaí that exits in the area, the urban area and the natural environment. The reality of the situation that the community of Igarapé da Fortaleza is facing are unplanned areas without urban infrastructure that generate damage to the area of environmental protection Fazendinha and the stream, not insuring quality of life for its residents or environmental conservation. The methodology is based on the diagnosis of the study area made through interviews with the local population, surveys and field research, and the data collected resulted in thematic maps, and there was still literature and documentary review. The result enables through the ecological landscaping the balance of the equation anthropogenic landscape and the environment integrating them consciously and sustainably.
Keywords: Arquitetura paisagística - Aspectos ambientais; Proteção ambiental; Planejamento ambiental; Igarapé da Fortaleza (Macapá, AP) - Aspectos econômicos; Área de Proteção Ambiental da Fazendinha - Igarapé da Fortaleza (Macapá, AP); Igarapé da Fortaleza (Macapá, AP) - Aspectos sociais; CNPQ::CIENCIAS SOCIAIS APLICADAS